Preparation of drip samples from leg of lamb with extended shelf life for nuclear magnetic resonance metabolomics studies. (February 2021) - Samuelsson, Linda M.; Olivecrona, Natalia; Cônsolo, Nara N.B.; Reis, Marlon M.; Reis, Mariza G.; Edwards, Patrick J.B.
Abstract: Metabolomics has been used for the analysis of meat samples for different applications. Using drip as a proxy for meat could offer an easy and non-invasive way of sampling meat, yielding a homogenous liquid sample easy to prepare for metabolomics analysis. There is currently no standard method for the preparation of drip samples for quantitative metabolomics. The aim of this study was to evaluate six different sample preparation methods for quantitative Nuclear Magnetic Resonance (NMR) metabolomics analysis of drip from a lamb leg with extended shelf life: centrifugation, ultrafiltration, and solvent precipitation using four different solvents or solvent mixtures. The six methods were evaluated based on protein removal efficiency, ability to quantify metabolites, metabolite concentrations, reproducibility, speed and relative cost. Three methods (ultrafiltration, solvent precipitation with either acetonitrile/acetone/methanol or chloroform/methanol) resulted in excellent protein removal, high concentrations of metabolites and high reproducibility and are therefore recommended for preparation of extended shelf life lamb leg drip samples for NMR metabolomics. Highlights: Six methods for preparing lamb drip for 1 H NMR spectroscopy were evaluated. Two solvent precipitation methods and ultrafiltration are recommended. Centrifugation resulted in insufficient protein removal and is not recommended.